Studies On Species Of Lactic Acid Bacteria Isolate Sr 12 From Bali Cattle Gastric With Conventional Method And Api Kit 50ch - Radwika, Made; Suardana, I Wayan; Sukrama, I Dewa Made (Journal of Veterinary and Animal Sciences; Vol 2 No 1 (2019)DO - 10.24843/JVAS.2019.v02.i01.p03, 2019)
Lactic acid bacteria (LAB) are Gram positive bacteria that characterized by non-motil, non-spore, negative catalase, coccus or bacillus cell shape, and live in microaerophilic condition with CO 2 aeration 5-7%. The purpose of study was to identifyy LAB isolate SR 12 isolated from gastrointestinal tract of bali cattle that previously known have potency as a source of probiotic.  The study initiated by cultivation of isolate on de Man, Rogosa, Sharpe (MRS) medium, confirmation of isolate with Gram staining and catalase test as a main procedure for Gram positive indentification. The next identification in order to know the species  of isolate was conducted both conventional test and kit API 50CH test. The result of study showed the LAB SR12 isolate as a genus of Pediococcus or Enterococcus according to its growth in temperature 10 o C, pH9,6 and it can’t grow in halophilic condition. On the other hands, the use of ofAPI kit 50CH test showed  the LAB SR12 was detected as Pediococcus pentosaceus .